Unusual neurological presentation of second stage African trypanosomiasis in a young boy: a case report - Etedal Ahmed A. Ibrahim; Mohammed Gasm Elseed M. Elmahal; Khabab Abbasher Hussien Mohamed Ahmed; Elfatih A. Hasabo; Mohammed Eltahier Abdalla Omer (BMC, 2022)
Abstract Background In South Sudan, sleeping sickness is a frequent condition caused by human African trypanosomiasis. There are two stages that are well-known. When the CNS is affected, especially with Trypanosoma gambiense infection, the early hemolymphatic stage and the late encephalitic stage have been observed, including mental, motor, and sensory symptoms. In this case, second-stage African trypanosomiasis manifested itself in an atypical neurological manner. Case presentation A 16-year-old boy from South Sudan referred to Sudan National Centre for Neurological Sciences, Khartoum, Sudan suffering from non-convulsive status epilepticus, mental deterioration and behavioral changes for the last nine months. He was conscious but disorientated. Low hemoglobin concentration, elevated ESR, enlarged spleen and positive card agglutination test for trypanosomiasis was found in this patient. Electro-encephalogram (EEG) found an on-going generalized seizure activity. The patient showed improvement after management with carbamazepine and tonic. Conclusion Our case highlights that late second stage African trypanosomiasis with neurological complications such as non-convulsive status epilepticus should be suspected in any patient who developed progressive cognitive decline and behavioral changes following long standing history of African Trypanosomiasis and routine Electro-encephalogram EEG is the best tool to diagnose non convulsive status epilepticus.